Debt and depth of recessions. - Park, Donghyun (Economics working papers.)
This paper empirically investigates the relationship between the speed of buildup of private debt (household and corporate) and the depth of recessions. To do this, we differentiate between financial recessions and normal recessions on the basis of how quickly their private debt builds up. In addition to output recessions, we look at consumption and investment recessions. We find that financial recessions are deeper than normal recessions in advanced economies−and the differences become even more pronounced when emerging market economies are added to the sample. Our evidence suggests that a buildup in corporate debt is especially damaging for emerging markets during financial recessions. A higher ratio of debt to gross domestic product in other words, less fiscal space exacerbates recessions only beyond a certain threshold level, suggesting a nonlinear effect. We find that the buildup of corporate debt and not just household debt can worsen recessions, especially in emerging market economies.